Novel Structure for E-business Through Dynamic Web Page Visualization - Singhal, Shefali; Tanwar, Poonam (Recent Patents on Engineering, 2021)
Nowadays when everything is digitalized, internet and web play a vital role in everyone’s life. When one has to ask something or has any online task to perform, one has to use the internet to access relevant webpages throughout. These webpages are mainly designed for large screen terminals. But due to mobility, convenience and economic reasons, most of the persons use Small Screen Terminals (SST) like mobile phone, palmtop, pagers, tablet computers and many more. Reading a web page which is actually designed for a large screen terminal on a small screen is time consuming and cumbersome task as there are many irrelevant content parts that are to be scrolled such as advertisements, etc. Here the main concern is e-business users. To overcome such issues, the source code of a web page is organized in a tree data-structure. Background: DOM and VIPS algorithms are the main background techniques supporting the current research. Objective: To restructure a web page in a more user friendly and content presenting format. Methods: In this paper, we have arranged each and every main heading as a root node and all the content of this heading as a child node of the logical structure. Using this structure, we have regenerated a webpage automatically according to the SST size. Results: Web page heading queue has been generated. Conclusion: The concept of logical structure supports every SST.
Keywords: backtracking